PKM Pengembangan Rumah Produksi - Elvy Sahnur Nasution; Rohana Rohana; Rizki Fadhillah Lubis (JURNAL PRODIKMAS Hasil Pengabdian Kepada Masyarakat, 2018)
Regumuk village community groups have planned to build a production house where production houses are planned to be used as a place for processing mangrove processing, but the construction of production houses is still abandoned due to lack of planning and design and funding for the construction of the production house. The Community Imaging Program (PKM) aims to develop production houses for community groups in the Regression Village that can be used for processing mangrove products, starting from mangrove materials, the exact technology used, and as a place for mangrove products after being cooked or produced so that community groups can produce mangrove products without having to wait for orders and can produce more and faster processed products. because activities can be done at any time of the day or night because of the night. With the development of production houses in stages, comfortable production houses can be produced and are expected to increase the production of processed mangrove communities while at the same time increasing community income. All activities provided to the Regemuk community are accompanied by experts. The activity is expected to help and accelerate the improvement of the community's economy. With sustainable PKM activities means sustainable community empowerment so that it can create a prosperous society.